Multiperspectivity in the Context of Design-Based Research: Theoretical-methodological Considerations to Reading Literacy at the End of Primary School - Drepper, Laura (EDeR. Educational Design Research, 2024)
This article demonstrates the value of multiperspectivity in Design-Based Research. Design principles for the development of the learning environment Lesen mit Rätseln are based on scientific and didactic findings on reading literacy. The design was implemented in a primary school with 35 fourth-graders over 10 weeks (SJ 2022/23). Quantitative and qualitative data are analysed to reconstruct reading literacy from multiple perspectives about reading fluency, reading comprehension, reading motivation and self-concept of reading. The objective is to value new evidence of reading literacy at the end of primary school and to evaluate the learning environment Lesen mit Rätseln. The paper ends with three scientifically proven and empirically evaluated design principles. These design principles refer to Deci & Ryan (1985) and can be applied to German Didactics. Finally, the design principles indicate advice for practice.